2019
DOI: 10.1515/ael-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Rationality of Historical Costs and Conservatism

Abstract: The principles characterizing the traditional revenue-expense approach to accounting cannot be traced back to a distinct event. I argue that they are ecologically rational. Their functionality is the result of cultural evolution, not of unitary human design. This is the reason why the efforts to defend them against the balance-sheet approach endorsed by standard-setters have encountered severe difficulties. Only the latter is clearly based on a coherent model of the economy, namely neoclassical economics. I fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
(59 reference statements)
0
6
0
2
Order By: Relevance
“…The driving force for the market tendency toward equilibrium is "the daring, imaginative, speculative actions of entrepreneurs who see opportunities for pure profit," and pure profit here is also referred as pure entrepreneurial profit (Kirzner, 1997). Braun (2016) and Basu and Waymire (2017) explicate the role of the traditional accounting principles in the market as an entrepreneurially driven process. Basu and Waymire (2017) argues that historical cost and conservatism jointly propel entrepreneurial discovery by helping a decision-maker to specify the set of profit opportunities given local conditions.…”
Section: Origin and Attribution Of Business Profitmentioning
confidence: 99%
“…The driving force for the market tendency toward equilibrium is "the daring, imaginative, speculative actions of entrepreneurs who see opportunities for pure profit," and pure profit here is also referred as pure entrepreneurial profit (Kirzner, 1997). Braun (2016) and Basu and Waymire (2017) explicate the role of the traditional accounting principles in the market as an entrepreneurially driven process. Basu and Waymire (2017) argues that historical cost and conservatism jointly propel entrepreneurial discovery by helping a decision-maker to specify the set of profit opportunities given local conditions.…”
Section: Origin and Attribution Of Business Profitmentioning
confidence: 99%
“…The case is also made in one way or another in Basu et al (2009), Basu and Waymire (2019), Braun (2019) and Sunder (2011).…”
Section: The Alleged Impact Of Standardisationmentioning
confidence: 99%
“…The last half-century or so has seen, across much of the developed world, a shift in institutional arrangements for devising accounting policies, from choice exercised by individual practitioners, albeit latterly within a structure involving increasing levels of authoritative, but ultimately non-mandatory guidance and influence, to mandatory standardisation. Some modern commentators (see, for example, Basu 2015;Braun 2019;Sunder 2011), argue that standardisation introduces an impetus that is, from an evolutionary standpoint, arbitrary, so that it overwhelms the progressive force of adaptation by selection based on fitness for the environment. This conclusion appears to justify calls for a return to accounting's 'prelapsarian' age of innocence, unspoilt by regulation or, at least, a reversal of the current direction of travel; such calls have been made by, among others, Benston et al (2006), Jamal and Sunder (2014), Myddelton (2004), Walker (2010) and West (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, the financial industry, the so-called "real economy" and governments have been struggling with the aftermath of the last financial crisis (e.g., Barth et al 2010;Rudolph 2010). Although there were multiple causes, government action in the form of more lenient monetary policy in combination with fair value accounting is seen as a major culprit (e.g., Huerta de Soto 2009; Hering et al 2010;Brösel et al 2012; on the problems of fair value accounting see further, e.g., Biondi 2011;Braun 2019). The European institutions have concluded that, in addition to close monitoring of the financial sector (e.g., Kaserer 2010;Davies 2015), the auditing market must also undergo fundamental changes.…”
Section: Introductionmentioning
confidence: 99%